The management of infected nonunion of tibia with a segmental defect using simultaneous fixation with a monorail fixator and a locked plate. (August 2018) - Gupta, S.; Malhotra, A.; Mittal, N.; Garg, S. K.; Jindal, R.; Kansay, R.
Abstract : Aims: The aims of this study were to establish whether composite fixation (rail-plate) decreases fixator time and related problems in the management of patients with infected nonunion of tibia with a segmental defect, without compromising the anatomical and functional outcomes achieved using the classical Ilizarov technique. We also wished to study the acceptability of this technique using patient-based objective criteria. Patients and Methods: Between January 2012 and January 2015, 14 consecutive patients were treated for an infected nonunion of the tibia with a gap and were included in the study. During stage one, a radical debridement of bone and soft tissue was undertaken with the introduction of an antibiotic-loaded cement spacer. At the second stage, the tibia was stabilized using a long lateral locked plate and a six-pin monorail fixator on its anteromedial surface. A corticotomy was performed at the appropriate level. During the third stage, i.e. at the end of the distraction phase, the transported fragment was aligned and fixed to the plate with two to four screws. An iliac crest autograft was added to the docking site and the fixator was removed. Functional outcome was assessed using the Association for the Study and Application of Methods of Ilizarov (ASAMI) criteria. Patient-reported outcomes were assessed using the Musculoskeletal Tumor Society (MSTS) score. Results: The mean age of patients was 38.1 years (sd 12.7). There were 13 men and one woman. The mean size of the defect was 6.4 cm (sd 1.3). the mean follow-up was 33.2 months (24 to 50). The mean external fixator index was 21.2 days/cm (sd 1.5). The complication rate was 0.5 (7/14) per patient. According to the classification of Paley, there were five problems and two obstacles but no true complications. The ASAMI bone score was excellent in all patients. The functional ASAMI scores were excellent in eight and good in six patients. The mean MSTS composite score was 83.9% (sd 7.1), with an MSTS emotional acceptance score of 4.9 (sd 0.5; maximum possible 5). Conclusion: Composite fixation (rail-plate) decreases fixator time and the associated complications, in the treatment of patients of infected nonunion tibia with a segmental defect. It also provides good anatomical and functional results with high emotional acceptance. Cite this article: Bone Joint J 2018;100-B:1094–9.